Measuring credit risk in family firms - Isabel Abinzano; Pilar Corredor; Beatriz Martinez (BRQ Business Research Quarterly, 2022)
This article attempts to identify the default risk measure which best reflects the idiosyncratic context of public family firms. Seven accounting- and market-based measures are compared over a sample of 981 US family and non-family firms for the period 2000-2016. The results show that the Black-Scholes-Merton (BSM) measure gives the best fit in both types of firm. However, all the accounting-based measures, especially Altman's Z-score, come closest to the market-based measures when used to assess the credit risk of family firms. The two types of measures also coincide more closely in their default risk orderings of family than of non-family firms. Useful practical implications can be drawn from these findings, which show that accounting-based measures can be used reliably in the absence of market data for family firms with similar characteristics to those in our sample.
Keywords: G32; G33; G13; C52; M21; M41; 650; Black-Scholes-Merton measure; default risk ranking of firms; family firms; Goodness of fit of credit risk